2010
DOI: 10.1007/s10974-010-9227-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates stretch-induced proliferation in C2C12 myoblasts

Abstract: Mechanical stretch of skeletal muscle activates nitric oxide (NO) production and is an important stimulator of satellite cell proliferation. Further, cyclooxygenase (COX) activity has been shown to promote satellite cell proliferation in response to stretch. Since COX-2 expression in skeletal muscle can be regulated by NO we sought to determine if NO is required for stretch-induced myoblast proliferation and whether supplemental NO can counter the effects of COX-2 and NF-kappaB inhibitors. C2C12 myoblasts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…While the orientati on of the myotube on the membrane would still affect the direction of deformation , the myotubes had a tendency to align in the same plane with maturati on and exposure to stretch as observed previousl y [22]. We have previously reported that cyclic stretching or L-NAME treatment of C2C12 cells does not reduce cell viability as measured by trypan blue exclusion [23]. Further, in the present study, counting of DAPI-stained nuclei indicate no differences in the total number of nuclei between groups (data not shown).…”
Section: Mechanical Stimulatio N Using Cyclic Strainsupporting
confidence: 50%
“…While the orientati on of the myotube on the membrane would still affect the direction of deformation , the myotubes had a tendency to align in the same plane with maturati on and exposure to stretch as observed previousl y [22]. We have previously reported that cyclic stretching or L-NAME treatment of C2C12 cells does not reduce cell viability as measured by trypan blue exclusion [23]. Further, in the present study, counting of DAPI-stained nuclei indicate no differences in the total number of nuclei between groups (data not shown).…”
Section: Mechanical Stimulatio N Using Cyclic Strainsupporting
confidence: 50%
“…PDTC has been shown to be effective at decreasing NF-ÎşB activation in C2C12 myotubes [68]–[71] and myoblasts [72] at concentrations ranging from 10 Îźm to 100 ÎźM. In order to observe this effect in proliferating C2C12 myoblasts, NF-ÎşB promoter activity and BrdU incorporation were measured following treatment with IL-1β or TNF-Îą, with and without 50 ÎźM PDTC.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a new publication indicates that nNOS is necessary in triggering an anabolic signaling pathway involving Nox4 and mTOR, which responds to overloading and regulates muscle hypertrophy (15). Furthermore, nitric oxide and NF-B were also found to be essential for stretch-induced proliferation of myoblasts (40). Indeed, inhibition of nitric oxide synthase has been shown to attenuate muscle remodeling and fiber-type shift in response to altered mechanical loading, whether the magnitude be increased or decreased (15,38,42).…”
Section: Discussionmentioning
confidence: 99%